Plato on the Limits of Human Life - Brill, Sara (Book collections on Project MUSE., 2013)
By focusing on the immortal character of the soul in key Platonic dialogues, the author shows how Plato thought of the soul as remarkably flexible, complex, and indicative of the inner workings of political life and institutions. As she explores the character of the soul, the author reveals the corrective function that law and myth serve. If the soul is limitless, she claims, then the city must serve a regulatory or prosthetic function and prop up good political institutions against the threat of the soul's excess. The author's sensitivity to dramatic elements and discursive strategies in Plato's dialogues illuminates the intimate connection between city and soul. -- Provided by publisher.